2019
DOI: 10.1016/j.sjbs.2019.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between PTEN and P62 gene expression in rat colorectal cancer cell

Abstract: ObjectiveAutophagy is a cellular pathway that regulates the transportation and degradation of cytoplasmic macromolecules and organelles towards lysosome, which is often related to the tumorigenesis and tumor suppression. Here, we investigate the regulating effect of PTEN gene on autophagy-related protein P62 in rat colorectal cancer (CRC) cells and explore the application value of PTEN gene in clinic.MethodsRat colorectal cancer was induced by intraperitoneal injection of 1,2-dimethyl hydrazine in male ACI rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Activation of mTOR and inhibition of autophagy was associated with abnormal accumulation of p62 in cancerous tissues [ 61 ]. Coinciding with this, the results of Zhang et al [ 62 ] revealed a dramatic elevation of the p62 expression in colon cancer tissues. In addition to suppressing autophagy, Brech et al [ 63 ] observed that activation of mTOR and AKT inhibited cellular apoptosis via phosphorylation of caspase-3 and caspase-9.…”
Section: Discussionsupporting
confidence: 63%
“…Activation of mTOR and inhibition of autophagy was associated with abnormal accumulation of p62 in cancerous tissues [ 61 ]. Coinciding with this, the results of Zhang et al [ 62 ] revealed a dramatic elevation of the p62 expression in colon cancer tissues. In addition to suppressing autophagy, Brech et al [ 63 ] observed that activation of mTOR and AKT inhibited cellular apoptosis via phosphorylation of caspase-3 and caspase-9.…”
Section: Discussionsupporting
confidence: 63%
“…Another study revealed that SFRP1 gene methylation in CRC was associated with lymph node invasion (50). On the other hand, PTEN has been widely studied as an indicator of CRC (18). A deeper look at the Tables 1 and 2 shows that relying on the set of genes that have already been identified as tumor markers (i.e.…”
Section: Normal Averagementioning
confidence: 99%
“…Relevant studies on these genes concluded that they could develop breast cancer (10)(11)(12)(13)(14)(15)(16)(17). Similarly, some genes, including PTEN, P62, NOD2, TP53, MSH3, POFUT1, RPRD1B, EIF6, MGP, FGF2, OGDHL, CYP24A1, WNT1, KLF5, WNT16, CLDN1, and TET3 have been effective in CRC development (18)(19)(20)(21)(22)(23)(24)(25). Analyzing any change in the expression of the genes can help in understanding the main causes of the disease and reveals at which state the disease is and how to handle it and plan proper and efficient treatments in numerous fields of application, such as drug designs (26) and personalized medicines (27).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, AsCas12a and the U6 promoter were successively cloned into the pCEP4 vector (Thermo Fisher, Waltham, MA, USA) with T4 ligase (M0569S, New England Biolabs) which contains the CMV promoter and the Orip/EBNA1 elements and can help obtain the COE plasmid (Figure S1). Plasmids were transformed into competent Escherichia coli DH5α (Tiangen, Beijing, China) for amplification [29]. Then, plasmid extraction was performed using the QIAGEN plasmid extraction kit (QIAGEN, Hilden, Germany).…”
Section: Design and Construction Of Episomal Crispr/cas12amentioning
confidence: 99%